2014
DOI: 10.1002/dev.21232
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of object versus location recognition in the rat: Acquisition and retention effects

Abstract: Novel object and location recognition tasks harness the rat’s natural tendency to explore novelty (Berlyne, 1950) to study incidental learning. The present study examined the ontogenetic profile of these two tasks and retention of spatial learning between postnatal day (PD) 17 and 31. Experiment 1 showed that rats ages PD17, 21, and 26 recognize novel objects, but only PD21 and PD26 rats recognize a novel location of a familiar object. These results suggest that novel object recognition develops before PD17, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
74
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(94 citation statements)
references
References 49 publications
(94 reference statements)
19
74
1
Order By: Relevance
“…In trial two, a plastic basketball (novel object; 6.4 cm W × 6.4 cm L × 6.4 cm H) replaced one of the first objects. This retention interval of 5 minutes was used to assess short-term memory, and previous studies have shown that neonatal and adolescent rats are able to perform the novel object recognition test with an interval of this length [44]. …”
Section: Methodsmentioning
confidence: 99%
“…In trial two, a plastic basketball (novel object; 6.4 cm W × 6.4 cm L × 6.4 cm H) replaced one of the first objects. This retention interval of 5 minutes was used to assess short-term memory, and previous studies have shown that neonatal and adolescent rats are able to perform the novel object recognition test with an interval of this length [44]. …”
Section: Methodsmentioning
confidence: 99%
“…Measurements of data from object recognition test, MWM, protein levels, and histological measures were analyzed by ANOVA for ‘sex' and ‘maternal treatment' followed by Duncan's post hoc test for each experimental group. For NOR one-sample t tests were used to compare exploration ratios of each group and ITI to an exploration ratio indicating no preference (0.5) [18]. Data for behavioral and protein measures are expressed as group means ± SEM and for histological measures as means ± SD.…”
Section: Methodsmentioning
confidence: 99%
“…The discrepancies may depend on the nature of the stressor and the time interval between the acquisition and retention trials. In juvenile males aged 35 days, neither controls nor PS rats showed significant NOR [5] in spite of the fact that others have shown that rats can recognize a novel object from 17 days of age [18]. …”
Section: Introductionmentioning
confidence: 99%
“…The paradigm is based on rodents’ innate preference for novel stimuli in their environments [11], and the many task variants within the paradigm can be used to assess different processes of incidental object, spatial, contextual, and temporal learning and memory [12, 13]. Novelty recognition paradigms are advantageous for studying the neurobiology of memory because they typically involve a one-trial training phase, and recognition memory has been shown to emerge during early development [14-17]. In adult rats, variants of this paradigm rely on different neural systems [13, 18], which makes these tasks particularly useful for investigating neurocognitive development.…”
Section: Introductionmentioning
confidence: 99%
“…Performance of the OR task emerges before postnatal day (PD) 17 in the rat [16, 17], whereas our lab demonstrated that the OL task, which relies on hippocampal function [12, 13, 16, 20, 21], emerges between PD17 and 21 [17]. Likewise, the CPFE, a form of contextual fear conditioning that also requires incidental context learning and the hippocampus [7, 22-24], ontogenetically emerges around the same time [7, 8, but see 25].…”
Section: Introductionmentioning
confidence: 99%